Arlo Smith for Attorney General Press Conference - Watkins, Howard::::::::: (1989)
Angled view of Seated: Don Fischbach, Robert Sears, Arlo Smith, Tom Bohigian, Judy Soley and 2 others; Standing: Mike Idiart, ?, ?, ?, Robert Perez, Holley Perez and Howard Watkins